Different Embolization Approaches for the Treatment of Posttraumatic Pseudoaneurysm of the Internal Maxillary Artery. Issue 8 (November 2018) - Granata, Francesca; Mormina, Enricomaria; Cinquegrani, Antonella; Cervino, Gabriele; Cicciù, Marco; Longo, Marcello; Nastro Siniscalchi, Enrico
Abstract : Abstract: Pseudoaneurysm is an abnormal dilation of an artery that could be caused either by iatrogenic or traumatic events and it is associated with high rupture risk. Pseudoaneurysm rarely involves internal maxillary artery. Computed tomography angiography and digital subtraction angiography are essential tools to perform a proper diagnosis and treatment of pseudoaneurysms. The authors described 2 different cases of internal maxillary artery pseudoaneurysm, treated by different embolization approaches. The first case was treated by a well-known arterial catheterism technique, whereas the second one was performed by an uncommon approach with a direct percutaneous puncture.